THE USE OF PROVERBS IN THE LORD OF THE RING BY TOLKIEN - Niyazova M. Kh.; Tuxtayeva M. A. (Web of Journals Publishing, 2023)
Proverbs are an important part of the complex language Tolkien created for Middle-earth: Tolkien as the narrator/author and many of his characters use them. This article discusses Tolkien's use of proverbs and includes the question of how and why he used proverbs when writing the novel.
Keywords: proverbs, The Lord of the Ring, J.R.Tolkien, proverbs in literature, traditional proverbs, Middle Earth.